Music Perception in Rhythmik Lessons - Pētersone, Ginta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The teaching of rhythmics was first introduced by the Swiss pedagogue Émile Jaques-Dalcroze, as he revealed the phenomenon of mutual interaction between music and movement, thus facilitating the musical, intellectual and physical growth of students. Music is one of the basic components in the choice of means of rhythmics. The perception of music is complex and it can be viewed both from the associative and the analytical aspect. The process of music perception in rhythmics is implemented with the help of movement. By assuming that movement is the basis of all live expression, musical rhythm becomes the movement synchronizer, thus acting on the sensomotoric, cognitive and emotional level. In the rhythmics lessons at the Emils Darzins Secondary Music School for grades 1-4 the process of music perception takes place both in an associative creative and an analytical way, thus ensuring an in-depth strengthening of skills and abilities acquired through music theory lessons and implementing rhythmics through lively and jovial action. The objective is to investigate the process of perception of rhythmic music classroom: music and movement interaction. Research methods: teaching observation, content analysis, test. Research base: Emils Darzins Music School 3rd and 4th grade students - total of 17. The study involved students names have been changed.